Neonatal resuscitation virtual training course: Use of an educational platform by medical students at a public university in Peru - Carlos A. Delgado; Blanca Solis-Chimoy; Milagro Raffo; Elia María Ortiz-Borda; Roberto Shimabuku (Educación Médica, 2023)
Introduction: Satisfactory performance in Neonatal Resuscitation requires continuous training, and several technologies can enhance its scope. This study was carried out to evaluate the use of an educational platform by medical students in a Neonatal Resuscitation virtual course. Materials and methods: Descriptive study with the data available on the Neonatal Resuscitation virtual course platform, evaluating the use of a population corresponding to the total number of undergraduate Medicine students from the Universidad Nacional Mayor de San Marcos (UNMSM) who enrolled as students to take the Paediatrics course in the last year of their studies during the years 2018 and 2019 in Lima, Peru. Results: Data from 379 sixth-year medical students in the 2018-I, 2019-I, and 2019-II semesters were included. Students entered the virtual course an average of 23 days before taking their online exam, and the average theory review time in the virtual system was 120 min. Students with outstanding performance in their scores completed 2 virtual exams, but there was no difference in the other characteristics. Conclusions: The sequence developed in the Neonatal Resuscitation virtual course, which begins with ''learn, see, and practice'', offers a greater capacity to retain the knowledge and skills acquired. The virtual offer of the theoretical component of Neonatal Resuscitation allows the use of innovative tools that make it possible to achieve a high performance of medical students when completing the virtual course of Neonatal Resuscitation. Resumen: Introducción: El desempeño satisfactorio en reanimación neonatal requiere entrenamiento continuo y diversas tecnologías pueden potenciar su alcance. Este estudio se realizó con el objetivo de evaluar el uso de una plataforma educativa por estudiantes de medicina en un curso virtual de Reanimación Neonatal. Material y Métodos: Estudio descriptivo con los datos disponibles en la plataforma de cursos virtuales de Reanimación Neonatal, evaluando el uso de una población correspondiente al total de estudiantes de pregrado de Medicina de la Universidad Nacional Mayor de San Marcos (UNMSM) que se inscribieron como estudiantes para cursar el curso de Pediatría en el último año de sus estudios durante los años 2018 y 2019 en Lima, Perú. Resultados: Se incluyeron datos de 379 estudiantes de 6to año de Medicina en los semestres 2018-I, 2019-I y 2019-II. Los estudiantes ingresaron al curso virtual un promedio de 23 días antes de realizar su examen en línea, y el tiempo promedio de revisión de teoría en el curso virtual fue de 120 minutos. Los estudiantes con desempeño sobresaliente es sus puntajes completaron dos exámenes virtuales, pero no hubo diferencia en las otras características. Conclusiones: La secuencia desarrollada en el curso virtual de Reanimación Neonatal, que inicia con “aprender, ver y practicar”, ofrece una mayor capacidad para retener los conocimientos y habilidades adquiridas. La oferta virtual del componente teórico de reanimación neonatal permite continuar con el uso de herramientas innovadoras que posibilitan lograr un alto desempeño de los estudiantes de medicina al completar el curso virtual de Reanimación Neonatal.